Morphine promotes the malignant biological behavior of non-small cell lung cancer cells through the MOR/Src/mTOR pathway - Xingyun Liu (BMC, 2021)
Abstract Background Morphine, a µ-opioid receptor (MOR) agonist, has been shown to be related to the activity of cancer cells, and a higher morphine dosage reduces the survival time of patients with lung cancer. However, the effect of morphine on the malignant behavior of lung cancer cells remains unclear. The aim of this study was to investigate the specific molecular mechanism by which morphine regulates the malignant biological behavior of non-small cell lung cancer. Methods Immunofluorescence staining and Western blot analyses were performed to detect MOR expression. H460 non-small cell lung cancer cells were used in this study, and cell proliferation, the cell cycle and apoptosis were evaluated using Cell Counting Kit-8 (CCK-8) and flow cytometry assays, respectively. Cell migration and invasion were detected using wound healing and Transwell assays. The effect of morphine on lung cancer development in vivo was examined by performing a xenograft tumor assay following morphine treatment. Results Morphine promoted the growth of H460 cells both in vivo and in vitro. Morphine enhanced cell migration and invasion, modified cell cycle progression through the S/G2 transition and exerted an antiapoptotic effect on H460 cells. Additionally, morphine increased Rous sarcoma oncogene cellular homolog (Src) phosphorylation and activated the phosphoinositide 3 kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway. Treatment with the MOR antagonist methylnaltrexone (MNTX) and the Src inhibitor protein phosphatase 1 (PP1) reduced the phosphorylation induced by morphine. Furthermore, MNTX, PP1, and the PI3K/AKT inhibitor deguelin reversed the antiapoptotic effect of morphine on lung cancer cells. Conclusion Morphine promotes the malignant biological behavior of H460 cells by activating the MOR and Src/mTOR signaling pathways.